2018
DOI: 10.1016/j.abb.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel miR17 /protein tyrosine phosphatase-oc/EphA4 regulatory axis of osteoclast activity

Abstract: Information about the molecular mechanisms leading to the activation of the osteoclast is relatively limited. While there is compelling evidence that the signaling mechanisms of Src and integrin β3 are essential for osteoclast activation, the regulation of these two signaling mechanisms is not fully understood. In this review, evidence supporting a novel regulatory axis of osteoclast activation that plays an upstream regulatory role in both the Src and integrin β3 signaling during osteoclast activation is disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…These authors also found that miR-128 specifically targets Sirt1 mRNA post-transcriptionally. Downregulation of miR-17 activates bone resorption by stabilizing protein tyrosine phosphatase receptor type O (Ptp-oc or Ptpro) mRNA and thereby downregulating EPHA4 receptor signaling, indicating the involvement in coupling [96]. Further, downregulation of miR-155 inhibits bone resorption [97], while upregulation of miR-106b inhibits bone resorption [98].…”
Section: Mirnas Regulating Osteoclast Function Survival and Apoptosismentioning
confidence: 99%
“…These authors also found that miR-128 specifically targets Sirt1 mRNA post-transcriptionally. Downregulation of miR-17 activates bone resorption by stabilizing protein tyrosine phosphatase receptor type O (Ptp-oc or Ptpro) mRNA and thereby downregulating EPHA4 receptor signaling, indicating the involvement in coupling [96]. Further, downregulation of miR-155 inhibits bone resorption [97], while upregulation of miR-106b inhibits bone resorption [98].…”
Section: Mirnas Regulating Osteoclast Function Survival and Apoptosismentioning
confidence: 99%
“…In agreement, transgenic mice that overexpress PTPROt in their OCLs exhibit a male-specific decrease in bone mass (29). Molecularly, PTPROt has been reported to activate Src in these systems by dephosphorylating the kinase at Tyr 527 (by chicken Src numbering) (27)(28)(29), thus stimulating downstream signaling events such as signaling by integrin 3, the kinase Syk, and Jun N-terminal kinase and nuclear factor B (30,31).…”
Section: Introductionmentioning
confidence: 77%
“…Upregulation of miR-29 is implicated in cytoskeletal organization-involved cell migration by targeting CDC42 and SLIT-ROBO Rho GTPase-activating protein 2 (SRGAP2), a negative regulator of Rac1 [ 129 ]. Downregulation of miR-17 is reported to increase the fusion of osteoclasts possibly via the miR-17-protein-tyrosine phosphatase- (PTP-) EphA4 axis or directly targeting vav guanine nucleotide exchange factor 3 (Vav3), thus promoting ITGB3-dependent Vav3-mediated activation of Rac1/Rac2 [ 140 ].…”
Section: Involvement Of Ncrnas In Osteoclast Differentiationmentioning
confidence: 99%
“…Downregulation of miR-17 elevates c-Src activation by targeting PTP, which dephosphorylates the inhibitory pY527 of c-Src to activate c-Src signaling. miR-20 and miR-92, which are also members of the miR-17~92 cluster genes, also have potential target sites on PTP mRNA, indicating the 13 Stem Cells International possibility that they play similar negative regulation roles in osteoclastogenesis to that of miR-17 [140,155].…”
Section: Nfi-amentioning
confidence: 99%